1994
DOI: 10.1182/blood.v83.4.958.bloodjournal834958
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomographic measurement of bone marrow blood flow to the pelvis and lumbar vertebrae in young normal adults [published erratum appears in Blood 1994 Nov 15;84(10):3602]

Abstract: Ten young normal adults had pelvic and lumbar vertebral body bone marrow blood flow examined using [15O]water and positron emission tomography (PET) in a study designed to assess the feasibility and reproducibility of the PET technique for measuring marrow blood flow to various marrow regions. The procedure was well tolerated. Repeated blood flow measurements obtained from two consecutive [15O]water exams on each individual subject were highly reproducible. In addition, there was minimal variation in marrow bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Similar to brain metastasis, in our study young patients also showed higher risk of bone metastasis. Possible mechanism of bone metastasis suggested to be is due to higher bone marrow flow along with circulating tumor cells in skeletal system in younger patients [ 35 , 36 ]. Our study gets supported by another recent lung cancer study which revealed that younger age was associated with the higher risk of bone metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to brain metastasis, in our study young patients also showed higher risk of bone metastasis. Possible mechanism of bone metastasis suggested to be is due to higher bone marrow flow along with circulating tumor cells in skeletal system in younger patients [ 35 , 36 ]. Our study gets supported by another recent lung cancer study which revealed that younger age was associated with the higher risk of bone metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental studies, positron emission tomography (PET) and single photon emission computed tomography have also been used to measure the blood flow in the bone often as a correlate of angiogenesis (Kahn et al 1994, Horger and Bares 2006, McCarthy 2006. PET has also been used to image the proteins that are implicated in the angiogenesis procedure (Beer and Schwaiger 2008).…”
Section: Introductionmentioning
confidence: 99%
“…5 Bone is a highly vascular mineral that produces adhesion molecules and is a source of angiogenic and bone resorbing molecules, all of which are conducive to the spread and development of tumors. 6,7 It also contains immobilized growth factors, which, when released, further enhance tumor cell proliferation. 8,9 Normal bone displays a dynamic environment involving tight regulation of reciprocating osteoblast and osteoclast activity, each complimenting each other in a continuous cycle of cell turnover.…”
mentioning
confidence: 99%